Cardiovascular Risk Is Increased in Miner’s Chronic Intermittent Hypobaric Hypoxia Exposure From 0 to 2,500 m? - Pedreros-Lobos, Andrés; Calderón-Jofré, Rodrigo; Moraga, Daniel; Moraga, Fernando A. (Frontiers in Physiology, 2021)
Over the past 40 years, mining activities in Chile have relocated miners who normally live at sea level to work at high altitudes. This results in a form of chronic intermittent hypobaric hypoxia (CIHH) characterized by alternating periods of work at high altitude and rest periods at sea level. Previous studies performed in our laboratory showed that aerobic capacity is reduced at 3,800 m, even when oxygen content is maintained. Our study aimed to determine the corporal composition, food intake, maximum oxygen uptake, and concentration of high sensitivity C reactive protein (hsCRP) in an acclimatized miner population that work from 0 to 2,500 m with CIHH exposure over 4 years. All miners recruited for our study were operators of heavy trucks with CIHH for over 4 years (shiftwork 7*7 days), and our experimental population was composed of 54 miners at sea level, 61 at 1,600 m, and 38 at 2,500 m. All evaluations were performed on the 3rd or 4th day of diurnal shiftwork. To determine corporal composition, we measured weight and height (to calculate body mass index, BMI), skinfolds (to calculate body fatty, BF), and waist circumference (WC); maximal aerobic capacity was evaluated using a ramp-incremental cycling to exhaustion protocol and a venous blood sample before the exercise test to measure (hsCRP) via an ELISA test. We found higher values of BMI, BF, and WC, in the miners’ population but observed no significant difference between populations. We found a decrease in VO2 of 11.6% at 1,600 m and 25.9% at 2,500 m compared to miners at sea level. An increase in (hsCRP) at 1,600 and 2,500 m regards sea level. We observed a high prevalence of overweight and obese subjects, which was related to the ad libitum availability of food and low physical activity (sedentarism). We found that work capacity was maintained despite a decreased VO2 max at moderate altitude. However, overweight and obesity support an increased risk of cardiometabolic disease in miner’s which is unrelated to altitude. In contrast, an increased hsCRP level could be associated with increased inflammatory mechanisms at 1,600 and 2,500 m.